Assessing the transport connectivity of urban territories, based on intermodal transport accessibility - Morozov, Aleksandr S.; Kontsevik, Georgii I.; Shmeleva, Irina A.; Schneider, Lasse; Zakharenko, Nikita; Budenny, Semen; Mityagin, Sergey A. (Frontiers in Built Environment, 2023)
By 2050, around 70% of people will live in urban areas. According to the 11.2 target of UN SDG “Sustainable cities and communities” to provide access to safe, affordable, accessible, and sustainable transport systems for all, the aim of the paper presented was to investigate accessibility and connectivity of urban territories by public transport systems. The main emphasis of the research was directed at transport infrastructure, which can be seen as sustainable, including public transport. The quality of life in a large city is determined by the ability to get from one destination to another quickly and efficiently. To implement this task a methodology has been developed to assess the connectivity and accessibility of urban areas. The method, based on an intermodal transport graph, is presented as an example of assessing accessibility and connectivity in different districts of Saint Petersburg (Russia), Helsinki (Finland), Stockholm (Sweden), and Amsterdam (Netherlands). The results are presented as graphs with clusters of city blocks presented as points. It is indicated that different areas of the city are connected through time values differently. The method can be used to make urban planning decisions about the provision of urban infrastructure, allows for ongoing monitoring of the situation, and filling in the gaps.